2016
DOI: 10.5114/reum.2016.62475
|View full text |Cite
|
Sign up to set email alerts
|

The use of magnetic fields in treatment of patients with rheumatoid arthritis. Review of the literature

Abstract: Magnetic fields are commonly used in therapies designed for subjects with rheumatic diseases, yet the effects of magnetotherapy are not entirely clear in these disorders.This study is designed to examine the literature investigating applications of magnetotherapy in the treatment of rheumatoid arthritis (RA).The review focused on publications related to administering magnetotherapy in patients with RA. The databases Science Direct, SpringerLink, Medline, PubMed, and Polska Bibliografia Lekarska were searched f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 17 publications
0
18
0
1
Order By: Relevance
“…A similar clinical effect was observed in osteotomy dogs, which were exposed to 0.3 mT and exhibited improved radiographic healing of osteotomy sites [ 43 ]. Intermediate SMF, i.e., 64 mT affected motor activity during sleep, reduced pain and allowed to reduce the administration of NSAIDs [ 33 ]. In addition, it was shown that 2 mT magnetic field was successfully used in arthritis treatment [ 44 ].…”
Section: Static Magnetic Field (Smfs) – a Potential Therapeutic Tool mentioning
confidence: 99%
“…A similar clinical effect was observed in osteotomy dogs, which were exposed to 0.3 mT and exhibited improved radiographic healing of osteotomy sites [ 43 ]. Intermediate SMF, i.e., 64 mT affected motor activity during sleep, reduced pain and allowed to reduce the administration of NSAIDs [ 33 ]. In addition, it was shown that 2 mT magnetic field was successfully used in arthritis treatment [ 44 ].…”
Section: Static Magnetic Field (Smfs) – a Potential Therapeutic Tool mentioning
confidence: 99%
“…The research on the use of HiSMF technology in magnetotherapy in clinics has been increasing due to its useful effects in many diseases, including cancers, edema, inflammation, wounds healing, and bone disorders [7][8][9][10]26]. Due to its safety and noninvasiveness, magnetotherapy has been approved as an instructive novel strategy by the US Food and Drug Administration (FDA) [16].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the use of MRI with 7 T in clinical diagnosis has been approved by the Food and Drug Administration (FDA) [6]. At the same time, the high-intensity magnetotherapy, a noninvasion approach, has been applied in the treatment of various diseases including osteoporosis [7], rheumatoid arthritis [8], diabetic wound healing [9], and cancer [10]. Therefore, the application of HiSMF medical equipment is megatrends in the near future.…”
Section: Introductionmentioning
confidence: 99%
“…Actually in vivo studies, both in mice and in humans, demonstrated that exposure of injured heart to EFs protects myocardium from the damages induced by oxidative stress, preserving metabolic activity in cardiomyocytes (Biały et al 2018, Ma et al 2013. Finally, although the mechanism of action is not completely understood yet, clinical studies in humans revealed that magnetic fields can be successfully applied, together with conventional therapies, for rheumatic diseases, anxiety, depression and pain care (Hattapoğlu et al 2019, Zwolińska et al 2016.…”
Section: Physical Energies and Biological Systemsmentioning
confidence: 99%